Brian2Loihi: An emulator for the neuromorphic chip Loihi using the spiking neural network simulator Brian - Michaelis, Carlo; Lehr, Andrew B.; Oed, Winfried; Tetzlaff, Christian (Frontiers in Neuroinformatics, 2022)
Developing intelligent neuromorphic solutions remains a challenging endeavour. It requires a solid conceptual understanding of the hardware's fundamental building blocks. Beyond this, accessible and user-friendly prototyping is crucial to speed up the design pipeline. We developed an open source Loihi emulator based on the neural network simulator Brian that can easily be incorporated into existing simulation workflows. We demonstrate errorless Loihi emulation in software for a single neuron and for a recurrently connected spiking neural network. On-chip learning is also reviewed and implemented, with reasonable discrepancy due to stochastic rounding. This work provides a coherent presentation of Loihi's computational unit and introduces a new, easy-to-use Loihi prototyping package with the aim to help streamline conceptualisation and deployment of new algorithms.